The liberation of L.B. Jones a story of Southern hospitality - Ford, Jesse Hill 1928- (Columbia Pictures Home Entertainment Inc., 2011)
Lord Byron Jones is a black businessman who owns a successful undertaking business, and is married to the very young and desirable Emma. His ability to cooperate with the white community is clearly an asset in the genteel town of Somerset, Tennessee. When Emma has an affair with a white policeman, divorce ensues and the stage is set for high drama
Orig.: USA, 1970
This disc is a DVD-R and may fail to play on some DVD equipment
Keywords: Crime films; Melodramas; Romance; Film adaptations; Melodrama; Verfilmung; Liebesfilm; Kriminalfilm; Ford, Jesse Hill / Film adaptations; Divorce / Tennessee / Drama; Man-woman relationships / Tennessee / Drama; Adultery / Tennessee / Drama; Interracial dating / Tennessee / Drama; Businesspeople, Black / Tennessee / Conduct of life / Drama; Southern States / Race relations / 20th century / Drama; Ford, Jesse Hill / https://id.oclc.org/worldcat/entity/E39PBJwhBmyxXfQwWDGdQG4yVC; Adultery; Divorce; Interracial dating; Man-woman relationships; Race relations; Southern States; Tennessee / https://id.oclc.org/worldcat/entity/E39PBJrRf39VjgwCHrPYYvMMfq; 1900-1999; Drama; Feature films; Fiction films; Films de fiction; Film; DVD-Video